The total substitution of fishmeal for poultry by-product meal supplemented with amino acids in diets for young Piaractus brachypomus, Cuvier 1818 (Orinoquia, 2014)
The aim of the present study was to determinate if poultry by-product meal (PBM) could substitute fish meal as protein ingredient in balanced diets for young Piaractus brachypomus (known as red-bellied pacu or white cachama) in controlled conditions. Three isoprotein/isoenergetic diets were formulated with 34% PBM and 4,160 Kcal/kg EB; treatment 1 (T1) contained 30% fishmeal as protein ingredient, treatment 2 (T2) 30% PBM and treatment 3 (T3) 30% PBM supplemented with aminoacids (lysine, methionine and threonine). 240 fry were selected, weighing 3 gr on average, and randomly distributed in 12 tanks each one with 500 litres (3 treatments per 4 repeats). Production parameters were measured (weight gain, feed intake, feed conversion rate, specific growth rate) and the cost of the diets being used. There were no significant differences between treatments regarding weight gain (1,233.2±156.1%), specific growth rate (5.06±2%) and feed conversion rate (1.22±0.09 gr). Feed in take was significantly lower in diet 1, compared to the other diets. Concerning costs, T1 was cheaper than the other treatments which increased by 4% for T3 and 5,8% for T2, there by showing that costs were similar and depended on the market situation of the different ingredients in the diets. The present study's results indicated that PBM could be used for feeding young white cachama without producing a negative effect concerning weight gain, feed conversion rate and specific growth rate and, since aminoacid supplements had no significant effects, using them on these diets for the species should not be necessary.Key words: Aminoacid; alternative source; nutrition; tropical fish; dietary supplement; white cachama/red-bellied pacu.
Keywords: Aminoacid; alternative source; nutrition; tropical fish; dietary supplement; white cachama/red-bellied pacu